The Booklover's Guide to New Orleans - Larson, Susan, 1951- (Book collections on Project MUSE., 2013)
The literary tradition of New Orleans spans centuries and touches every genre; its living heritage winds through storied neighborhoods and is celebrated at numerous festivals across the city. For booklovers, a visit to the Big Easy isn't complete without whiling away the hours in an antiquarian bookstore in the French Quarter or stepping out on a literary walking tour. Perhaps only among the oak-lined avenues, Creole town houses, and famed hotels of New Orleans can the lust of A Streetcar Named Desire, the zaniness of A Confederacy of Dunces, the chill of Interview with the Vampire, and the heartbreak of Walker Percy's Moviegoer begin to resonate.